2019
DOI: 10.4103/lungindia.lungindia_434_17
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exacerbation of asthma: An intrinsic phenotype of uncontrolled asthma

Abstract: Asthma is a chronic disease of the airways affecting a large number of people across the globe. Uncontrolled asthma poses an emotional as well as the physical burden on patients and results in a great economic burden. “Exacerbation-prone phenotype” asthmatics are a cluster of patients who may suffer from more frequent and severe exacerbations than other asthmatics. Factors such as inadequate symptom control, improper adherence to medications, and incorrect use of inhalers are responsible for frequent asthma ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…On the basis that increased SABA use is a marker of poor asthma control [ 1 ], it is possible that this group of paediatric patients who may suffer more frequent and severe exacerbations have exacerbation-prone phenotypes [ 34 ]. Current asthma treatment and prevention strategies increasingly emphasise the need to improve asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis that increased SABA use is a marker of poor asthma control [ 1 ], it is possible that this group of paediatric patients who may suffer more frequent and severe exacerbations have exacerbation-prone phenotypes [ 34 ]. Current asthma treatment and prevention strategies increasingly emphasise the need to improve asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…They can also increase self-efficacy (63) and create positive self-management behavioral changes like inhaler use, medication adherence, regular exercise, and followup visits (63,64). They can drive understanding and knowledge (64,65), and bring about reductions in both the inappropriate usage of medications and unscheduled visits (31). It was also observed that such self-management programmes facilitate the identification of hurdles to self-management, and they can inform strategies that can improve understanding and health literacy (28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a group of asthmatic patients called exacerbation-prone phenotype who experience even more frequent and severe exacerbations than other ones. [13] Beyond the clinical impact of the disease, an important economic burden is also observed. [6,14,15] A total annual average cost (both direct and indirect costs) of 2208 Brazilian Real (BRL) per patient over the period 2008 to 2013 was estimated for Brazilian patients followed in the public healthcare system.…”
Section: All Data Generated or Analyzed During This Study Are Include...mentioning
confidence: 99%
“…Furthermore, there is a group of asthmatic patients called exacerbation-prone phenotype who experience even more frequent and severe exacerbations than other ones. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%